2011
DOI: 10.1111/j.1365-2621.2011.02730.x
|View full text |Cite
|
Sign up to set email alerts
|

Kigelia africana seed: proximate, mineral, vitamin E, fibre, amino acid and fatty acid composition

Abstract: Research reports on the ethnomedical and pharmacological potential of Kigelia africana extracts. In this study, the nutritional potential of K. africana seed and seed oil was evaluated by chemical analyses. Organic matter and ash constituted 915.23 ± 7.98 g kg )1 DM and 49.05 ± 4.55 g kg )1 DM of the seed mass, respectively. Oil constituted 492.2 g kg )1 DM of the seed mass with oleic acid, linoleic acid and a-linolenic acid constituting 17.6%, 12.9% and 54.3%, respectively, of the seed oil. Vitamin E concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Although lower than the oil yield from sunflower and cotton seed, oil yield from M. caffra seed (26%) is comparable to soybean. When compared to M. zeyheri, its upland cousin, whose seed has a reported seed oil yield of 21.3% (Chivandi et al, 2011a(Chivandi et al, , 2011b, M. caffra seed has a higher seed oil yield. Due to its interesting fatty acid profile, the potential of M. caffra seed oil as a novelty raw material for community-based cottage industries needs to be explored.…”
Section: Potential As a Non-conventional Plant Oil Sourcementioning
confidence: 89%
See 1 more Smart Citation
“…Although lower than the oil yield from sunflower and cotton seed, oil yield from M. caffra seed (26%) is comparable to soybean. When compared to M. zeyheri, its upland cousin, whose seed has a reported seed oil yield of 21.3% (Chivandi et al, 2011a(Chivandi et al, , 2011b, M. caffra seed has a higher seed oil yield. Due to its interesting fatty acid profile, the potential of M. caffra seed oil as a novelty raw material for community-based cottage industries needs to be explored.…”
Section: Potential As a Non-conventional Plant Oil Sourcementioning
confidence: 89%
“…The full fat Mimusops zeyheri seed, an upland cousin of M. caffra, had a reported CP content of 9.3% (Chivandi et al, 2011a) which is comparable to that of the CP content of full fat M. caffra seed. However, when compared to the CP content of full fat seeds from other indigenous fruit bearing trees found in SSA, for example, Kigelia africana at 37.5% (Chivandi et al, 2011b), Ximenia caffra at 18.3% (Chivandi et al, 2012) and Terminalia sericea at 46.2% (Chivandi et al, 2013), M. caffra seed has lower CP content. When compared to conventional dietary protein sources for feeds such as soybean meal, cotton and sunflower seed meal, the M. caffra seed has both a low CP content and a poor amino acid profile characterised by low concentrations of essential amino acids.…”
Section: Potential As Food/feed Ingredientmentioning
confidence: 94%
“…Thus, the inclusion of K. africana, at the levels used in the current study did not increase the growth of male O. andersonii. Chivandi et al (2011) recommended K. africana as potential supplement for fish growth due to its substantial proportions of nutrients, such as lipid (49.2%) and crude protein (35.7%). Nevertheless, such nutrients can be directed towards gonadal development instead of overall growth since fish can prioritize the available resources for various body functions, such as basal metabolism, movement, immune system, growth, and reproduction (Salze et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The Red milkwood ( Mimusops zeyheri), an IFBT, is widely distributed in SSA ( Janick & Paull, 2008 ) and its fruit pulp is consumed by animals, birds and humans ( Chivandi, Davidson, Pretorius & Erlwanger, 2011 ). Findings from our laboratory have shown that the seed meal from dehulled M. zeyheri seed has a protein content (9.3%) similar to that of maize but a higher energy (24.34±0.56 MJ/kg DM vs 17 MJ/kg DM) and calcium content ( Chivandi, Davidson & Erlwanger, 2011 ). Thus M. zeyheri seed meal can potentially be used as a calcium-rich dietary energy source in quail feeds.…”
Section: Introductionmentioning
confidence: 98%